2009
DOI: 10.1007/s10597-009-9273-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Community-Based Intervention for Parents with FASD

Abstract: The purpose of this study was to evaluate the effectiveness of the Step by Step program in which mentors work with parents affected by Fetal Alcohol Spectrum Disorder (FASD) on a one-to-one basis. Mentors help clients identify and work towards meeting their needs and achieving their goals. Data from 24 closed client files was collected and analyzed and as predicted, the program was effective in helping clients reduce their needs and achieve their goals. The clients' reason for leaving the program as well as wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Case accounts of individuals with FASD have shown that postsecondary education and consistent employment outcomes are possible (e.g., Boyle Street Education Centre 2007;Community Living British Columbia 2011;Erb 2015). However, the literature is generally reflective of lower expectations of adult development for youth with FASD, noting that memory challenges and social challenges contribute to learning and health difficulties for many (Coles et al 2010;Denys et al 2011;O'Connor and Paley 2009). However, educational and occupational opportunities can be facilitated through community-based initiatives that inform adults and their caregivers about appropriate programs (Grant et al 2004;Denys et al 2011).…”
Section: Upport Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Case accounts of individuals with FASD have shown that postsecondary education and consistent employment outcomes are possible (e.g., Boyle Street Education Centre 2007;Community Living British Columbia 2011;Erb 2015). However, the literature is generally reflective of lower expectations of adult development for youth with FASD, noting that memory challenges and social challenges contribute to learning and health difficulties for many (Coles et al 2010;Denys et al 2011;O'Connor and Paley 2009). However, educational and occupational opportunities can be facilitated through community-based initiatives that inform adults and their caregivers about appropriate programs (Grant et al 2004;Denys et al 2011).…”
Section: Upport Servicesmentioning
confidence: 99%
“…In general, extensive and diffuse alcohol effects result in significant disabilities that require intensive and longerterm support (Fagerlund et al 2011). It has been noted, for example, that memory problems persist from childhood into young adulthood (Coles et al 2010) and that children with FASD will have elevated rates of mental health problems as young adults (Denys et al 2011;O'Connor and Paley 2009). Anecdotally, however, as reflected in several case accounts, a high quality of life is possible (e.g., Boyle Street Education Centre 2007; Community Living British Columbia 2011;Erb 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grant et al [65] found improved outcomes in the areas of substance use, contraceptive use, use of medical and mental health services, and improvements in maintaining stable housing arrangements. In a related study, Denys et al [66] found that a similar mentoring program for parents with FASD [n=24] was effective in helping clients reduce their needs and achieve their goals, particularly in the areas of social problems, experience of abuse, housing, transportation, self-care, and health.…”
Section: Mentoring Supportsmentioning
confidence: 99%
“…Gender differences were noted in that females were found to have higher prevalence rates of depression (50 %) and anxiety (50 %) than males (40 % and 0 %, respectively). In a Canadian study of 24 adults with PAE participating in an intervention program, Denys et al [49] found that 83 % had at least one mental health diagnosis, with the most common being depression, anxiety, or ADHD.…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%